GE_GERICHTE C/10593/2013 vom 21. Juli 2015 - GE Cour de justice (2015)
CONVENTION COLLECTIVE DE TRAVAIL; CONTRAT DE TRAVAIL; VACANCES; INDEMNITÉ DE VACANCES | CO.329a.1; CO.329d.1; CO.329c.1; CO.128.3; CO.130.1; CO.329c.2